Syncope: finding the cause of the drop 2 - Olshansky, Brian (Henry Stewart Talks, 2015)
Challenge #4: determining who needs aggressive management, Challenge #5: treating the problem, Pacemakers as a treatment, ACC/AHA guidelines, Challenge #6: restricting the patient
Reviewed at 2021/01/10